2011
DOI: 10.1016/j.kjms.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in patients with urinary stones of varying compositions

Abstract: Kidney stones are a potential risk factor for chronic kidney disease. The impact of different urinary stone components on renal function is unknown. In this study, we retrospectively reviewed 1,918 medical records of patients with urolithiasis. The renal function was evaluated as estimated glomerular filtration rate. All the stones were analyzed by Fourier transform infrared spectroscopy. The patients were divided into five groups according to the stone components. Statistical analysis was performed with analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
(26 reference statements)
2
25
0
Order By: Relevance
“…This is indeed an intriguing observation and integrates the concept of hyperuricemia and its association with the metabolic syndrome with nephrolithiasis-associated CKD risk. It should be noted that these findings were consistent with another study from Taiwan that showed that patients with noncalcium-based nephrolithiasis (struvite and uric acid) were more likely to have eGFR less than 60 ml/min/1.73 m 2 [20]. The association with struvite stones has been attributed to recurrent urinary tract infections.…”
Section: Risk Of Chronic Kidney Disease Due To Nephrolithiasissupporting
confidence: 87%
“…This is indeed an intriguing observation and integrates the concept of hyperuricemia and its association with the metabolic syndrome with nephrolithiasis-associated CKD risk. It should be noted that these findings were consistent with another study from Taiwan that showed that patients with noncalcium-based nephrolithiasis (struvite and uric acid) were more likely to have eGFR less than 60 ml/min/1.73 m 2 [20]. The association with struvite stones has been attributed to recurrent urinary tract infections.…”
Section: Risk Of Chronic Kidney Disease Due To Nephrolithiasissupporting
confidence: 87%
“…There are many studies that associate stone disease with varying degrees of renal insufficiency, patients with CKD present 0.8% to 17.5% of those presenting with urinary stone disease [13] . DM and HT, well-defined risk factors, were considerably related with renal impairment in patients with urinary stone [4,12] .…”
Section: Minireviewsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a significant health issue that affects 13% of the adults in the United States. The potential reasons of renal failure in patients with urolithiasis are multifactorial and enclose hydronephrosis, infection, DM, hypertension (HT), repeated stone surgeries, eating habits, environmental, and genetic factors [12] . There are many studies that associate stone disease with varying degrees of renal insufficiency, patients with CKD present 0.8% to 17.5% of those presenting with urinary stone disease [13] .…”
Section: Minireviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, gender has been proven to be a crucial factor-proportion of kidney stone incidence in males compared to females is about 2-4:1 [5,6]. Testosterone has been proposed as the key factor responsible for the male preference of this disease [7].…”
Section: Introductionmentioning
confidence: 99%